Outcome reporting bias in Cochrane systematic reviews: a cross-sectional analysis. Issue 3 (16th March 2020) - Shah, Kieran; Egan, Gregory; Huan, Lawrence (Nichoe); Kirkham, Jamie; Reid, Emma; Tejani, Aaron M
Abstract : Background: Discrepancies in outcome reporting (DOR) between protocol and published studies include inclusions of new outcomes, omission of prespecified outcomes, upgrade and downgrade of secondary and primary outcomes, and changes in definitions of prespecified outcomes. DOR can result in outcome reporting bias (ORB) when changes in outcomes occur after knowledge of results. This has potential to overestimate treatment effects and underestimate harms. This can also occur at the level of systematic reviews when changes in outcomes occur after knowledge of results of included studies. The prevalence of DOR and ORB in systematic reviews is unknown in systematic reviews published post-2007. Objective: To estimate the prevalence of DOR and risk of ORB in all Cochrane reviews between the years 2007 and 2014. Methods: A stratified random sampling approach was applied to collect a representative sample of Cochrane systematic reviews from each Cochrane review group. DOR was assessed by matching outcomes in each systematic review with their respective protocol. When DOR occurred, reviews were further assessed if there was a risk of ORB (unclear, low or high risk). We classified DOR as a high risk for ORB if the discrepancy occurred after knowledge of results in the systematic review. Results: 150 of 350 (43%) review and protocol pairings contained DOR. When reviews were further scrutinised, 23% (35 of 150) of reviews with DOR contained a high risk of ORB, with changes being made after knowledge of results from individual trials. Conclusions: In our study, we identified just under a half of Cochrane reviews with at least one DOR. Of these, a fifth were at high risk of ORB. The presence of DOR and ORB in Cochrane reviews is of great concern; however, a solution is relatively simple. Authors are encouraged to be transparent where outcomes change and to describe the legitimacy of changing outcomes in order to prevent suspicion of bias.